Bridging the age-based digital divide through inclusive design: an action research on the adoption of inclusive design in small e-government context - Hammad, Faisal (2017)
This research looks at using Inclusive Design as mean to bridge the age-based digital divide, by conducting Action research in a Local Council in the UK. Research on the digital divide looks at the inequality in technology access between different demographical characteristics. While this is very useful to highlight access inequality, it fails to address the steps required to bridge the gap. Some research even suggested that the digital divide is bridged and that research in this field is irrelevant. This is due to the narrow focus of some researchers about the digital divide. The focus should be not on whether older people possess Information and Communications Technology (ICT) products; it should be on how they use their products and what we can do to improve the person-technology fit. On the other hand, inclusive design has been a main driver to ensure that buildings and products do not prohibit people with disabilities from utilising the building or product. However, there is limited research about the extension of inclusive design practices in Information Systems (IS), particularly interface design and system design. Most of the current design guidelines and best practices do not provide a holistic view of the inclusive design process, thus leaving the designers on their own in terms of producing an easy interface for users, by just merely implementing the accessibility guidelines provided by the W3C to ensure inclusivity of the website or online service. Assuming that inclusivity is reached only by including screen readers and magnified modes to prospective users.